Gene Discovery in the Apicomplexa as Revealed by EST Sequencing and Assembly of a Comparative Gene Database - Li, Li; Brunk, Brian P.; Kissinger, Jessica C.; Pape, Deana; Tang, Keliang; Cole, Robert H.; Martin, John; Wylie, Todd; Dante, Mike; Fogarty, Steven J.; Howe, Daniel K.; Liberator, Paul; et al. (Genome Research, 2003)
Large-scale EST sequencing projects for several important parasites within the phylum Apicomplexa were undertaken for the purpose of gene discovery. Included were several parasites of medical importance (Plasmodium falciparum, Toxoplasma gondii) and others of veterinary importance (Eimeria tenella, Sarcocystis neurona, and Neospora caninum). A total of 55,192 ESTs, deposited into dbEST/GenBank, were included in the analyses. The resulting sequences have been clustered into nonredundant gene assemblies and deposited into a relational database that supports a variety of sequence and text searches. This database has been used to compare the gene assemblies using BLAST similarity comparisons to the public protein databases to identify putative genes. Of these new entries, ∼15%–20% represent putative homologs with a conservative cutoff of p < 10−9, thus identifying many conserved genes that are likely to share common functions with other well-studied organisms. Gene assemblies were also used to identify strain polymorphisms, examine stage-specific expression, and identify gene families. An interesting class of genes that are confined to members of this phylum and not shared by plants, animals, or fungi, was identified. These genes likely mediate the novel biological features of members of the Apicomplexa and hence offer great potential for biological investigation and as possible therapeutic targets.[The sequence data from this study have been submitted to dbEST division of GenBank under accession nos.:Toxoplasma gondii: BG657138–BG661027,BI921045–BI921090, BI946571–BI946588, BM003839–BM004582,BM039066– BM040645, BM131233–BM133172, BM174962–BM176879,BM188953–BM189923, BM271559–BM271694. Plasmodium falciparum:BI670521–BI670830, BI813842–BI816393, BI936022–BI936312,BM273300–BM276553. Sarcocystis neurona: BE574328, BE574347,BE574384, BE574386, BE574409, BE574465, BE574508, BE574543, BE574561,BE574633, BE574689, BE574694, BE574723, BE635418–BE636244,BE574288–BE574724, BF323572–BF324064, BM252128–BM253024,BM303125–BM305293. Eimeria tenella: AI755306–AI758088,AI759179–AI759181, AI759254–AI759304, AI759182–AI759253, AI759305–AI759387, AI759463–AI759546,AI759388–AI759462, AI759547–AI759621, BE027133– BE028807,BF023640–BF023711, BF023609–BF023639, BG235514–BG235880,BG413067–BG413336, BG466192–BG467045, BG515959–BG517044,BG560819–BG562379, BG724474–BG725148, BI895002–BI896127,BM305294–BM306971, BM321464–BM322026. Neospora caninum: BF248514–BF249435, BF716421–BF717094, BF823742,BF823805– BF823813, BF823743–BF824633, BG235070–BG235513.]
10.1101/gr.693203